Road-killed wild animals: a preservation problem useful for eco-epidemiological studies of pathogens - Richini-Pereira, V. B. [UNESP]; Bosco, S. M. G. [UNESP]; Theodoro, R. C. [UNESP]; Barrozo, L.; Bagagli, Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2010)
Road-killed wild animals have been for years used for surveillance of vectors of zoonotic pathogens and may offer new opportunities for eco-epidemiological studies. In the current study, fungal infection was evaluated by PCR and nested-PCR in tissue samples collected from 19 road-killed wild animals. The necropsies were carried out and samples were collected for DNA extraction. Results, using PCR with a panfungal primer and nested PCR with specific primers, indicated that some animals are naturally infected with Amauroascus aureus, Metarhizium anisopliae, Aspergillus flavus, Aspergillus oryzae, Emmonsia parva, Paracoccidioides brasiliensis or Pichia stipitis. The approach employed herein proved useful for detecting the environmental occurrence of several fungi, as well as determining natural reservoirs in wild animals and facilitating the understanding of host-pathogen relationships.
Keywords: road-killed animals; fungal pathogens; eco-epidemiology; PCR